PENGARUH WORKLIFE BALANCE LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAAN PT BANK SULSELBAR KANTOR PUSAT MAKASSAR - Agrisya Agrisya Yuliana (Universitas Teuku Umar, 2026)
This study aims to examine the influence of work-life balance, work environment, and leadership style on employee performance at PT Bank Sulselbar Makassar Head Office. Using a quantitative sampling method, the study recruited 77 respondents, determined using the Slovin formula. Data analysis was conducted using multiple linear regression.Partial test results indicate that work-life balance (0.001) and work environment (0.001) have a positive and significant effect on employee performance. Conversely, leadership style (0.284) does not have a statistically significant effect on performance. However, simultaneously, these three variables significantly influence employee performance (0.000). The coefficient of determination (R2) of 0.813 indicates that this model explains 81.3% of the variation in employee performance, with the remaining 18.7% explained by other variables outside the study. These results indicate that to increase productivity at the banking head office, management needs to prioritize work-life balance policies and maintain a conducive work environment.Keywords: Work-life Balance, Work Environment, Leadership Style, Employee Performance.